Google Classroom Aided Instruction on Student Teachers' Mathematics Achievement in Owerri, Nigeria - Alwell, Uzoma; Uwakwe, Joy Ijeoma; Ike, Iheanacho Chukwudi; Ogunleke, Isaac Adekunle (Brillo Journal, 2023)
The study investigated the effect of Google Classroom aided instruction on students’ achievement on Mathematics Courses of 2019-2021 academic sessions in Alvan Ikoku University of Education, Owerri. Guided with three research questions and three null hypotheses to establish significant difference in the mathematics achievement scores of students with Google Classroom aided instruction compared with those taught without the platform. Quasi-experimental design of non-randomised control group design was adopted. The population of the study comprises of all students of the university, offering Mathematics courses in Department of Mathematics with a population size of 331 students with a sample of 127 students. The instrument for data collection were moderated examination question papers and course lecturer made test questions. Data collected were analysed using mean, standard deviation and t-test of equality of mean. Major results showed that male students achieved significantly than the female students in the mathematics courses, students taught without the aid of Google classroom platform achieved significantly than those in the Google classroom aided instruction class. Also, the use of Google classroom aided instruction does not result to gender disparity in Mathematics achievement. Hence, it was recommended for further research on factors affecting effective utilization of Google classroom and remedies.